2013
DOI: 10.1128/jvi.02368-12
|View full text |Cite
|
Sign up to set email alerts
|

CD22 Is Required for Protection against West Nile Virus Infection

Abstract: West Nile virus (WNV) is a RNA virus of the family Flaviviridae and the leading cause of mosquito-borne encephalitis in the United States. Humoral immunity is essential for protection against WNV infection; however, the requirements for initiating effective antibody responses against WNV infection are still unclear. CD22 (Siglec-2) is expressed on B cells and regulates B cell receptor signaling, cell survival, proliferation, and antibody production. In this study, we investigated how CD22 contributes to protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
1

Year Published

2013
2013
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 61 publications
1
22
1
Order By: Relevance
“…Conversely, CD22 has been shown to play a role in controlling a viral infection. CD22-deficient mice are more susceptible to West Nile Virus (WNV) infection, after which there was normal anti-WNV antibody production but decreased WNV-specific CD8 + T cell responses compared to wild type mice, including decreased lymphocyte migration into the draining lymph nodes [22].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, CD22 has been shown to play a role in controlling a viral infection. CD22-deficient mice are more susceptible to West Nile Virus (WNV) infection, after which there was normal anti-WNV antibody production but decreased WNV-specific CD8 + T cell responses compared to wild type mice, including decreased lymphocyte migration into the draining lymph nodes [22].…”
Section: Discussionmentioning
confidence: 99%
“…WNV-specific IgM and total IgG levels were determined by an ELISA using a purified recombinant WNV E protein as described [ 20 ]. In some experiments the quantities of serum WNV E-specific IgM and IgG between WT mice and BAFFR -/- mice were determined using the endpoint titer determination method [ 67 ]. In other experiments, to determine the specific amount of WNV E-specific IgM and IgG an adaptation of a previously described ELISA was used [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…That provided a potential therapeutic target to restore the immune homeostasis in sepsis ( 27 ). What is more, a recent Siglec-2 −/− mice study confirmed that Siglec-2 helped to control West Nile virus infection through CD8 T cells response, promoted lymphocyte migration into the draining lymph nodes, and affected chemotaxis via controlling chemokine production ( 28 ). Siglec-2 specific immunotoxins have been used in clinical studies for hairy cell leukemia and autoimmune diseases ( 29 , 30 ), however, studies on the sepsis is still lacking.…”
Section: Siglec-2mentioning
confidence: 99%